Pacific white shrimp, red drum, and tilapia integrated in a biofloc system: Use of tilapia as a consumer of total suspended solids - Poersch, Luis (2021)
The objective of this study was to evaluate tilapia, Oreochromis niloticus, for the biological control of suspended solids in an integrated biofloc technology (BFT) system rearing red drum, Sciaenops ocellatus, and Pacific white shrimp, Litopenaeus vannamei. Four integrated systems were structured with recirculating water in closed circuits composed of separate tanks for each species. The experiment compared the use of tilapia to control suspended solids (biological treatment [BT]) to control systems without tilapia. The initial mean weights and stocking densities were: 2 g and 250 ind/m3 for shrimp; 71 g and 1.04 kg/m3 for red drum; and 85 g and 5.12 kg/m3 for tilapia. Temperature, dissolved oxygen (DO), pH, alkalinity, salinity, total suspended solids, total ammonia nitrogen (TA-N), and nitrite were measured. Temperature, DO, pH, alkalinity, and TA-N were maintained within guidelines recommended for shrimp, red drum, and tilapia. Nitrite concentrations remained within guidelines for red drum and tilapia. No significant difference in growth performance between the control and BT was observed, but the apparent consumption of solids in systems with tilapia resulted in decreased particulate matter in the effluent compared to the control. The study showed that the tilapia could control the suspended solids when integrated with red drum and marine shrimp culture with BFT in an integrated multitrophic system.